Sézary syndrome managed with histone deacetylase inhibitor followed by anti‐CCR4 monoclonal antibody. (1st April 2018) - Numata, T.; Nagatani, T.; Shirai, K.; Maeda, T.; Mae, K.; Nakasu, M.; Saito, M.; Usuda, T.; Tsuboi, R.; Okubo, Y.
Summary: A 70‐year‐old man presented to our clinic with a 10‐year history of recurrent pruritic erythema and plaques on his trunk and limbs. Based on the pathological findings and monoclonal rearrangement of the T‐cell receptor (TCR)–Cβ1 gene, mycosis fungoides (T2N0M0B0 stage IB) was diagnosed. Despite combination therapy including histone deacetylase inhibitor (vorinostat), the symptoms slowly evolved into Sézary syndrome (SS; T4N1M0B2) over 4 years, with dense infiltrates due to atypical lymphocytes expressing CCR4 developing in the entire dermis. Anti‐CCR4 monoclonal antibody (mogamulizumab) treatment was started. After seven courses, the CCR4‐positive atypical lymphocytes decreased in the dermis to levels below those seen at the outset of treatment. To our knowledge, there is no previous report of a case of SS managed with vorinostat followed by mogamulizumab demonstrating such a remarkable change in the pathological state following treatment.